Depth perception: cuttlefish (Sepia officinalis) respond to visual texture density gradients - Josef, Noam (2018)
Studies concerning the perceptual processes of animals are not only interesting, but are fundamental to the understanding of other developments in information processing among non-humans. Carefully used visual illusions have been proven to be an informative tool for understanding visual perception. In this behavioral study, we demonstrate that cuttlefish are responsive to visual cues involving texture gradients. Specifically, 12 out of 14 animals avoided swimming over a solid surface with a gradient picture that to humans resembles an illusionary crevasse, while only 5 out of 14 avoided a non-illusionary texture. Since texture gradients are well-known cues for depth perception in vertebrates, we suggest that these cephalopods were responding to the depth illusion created by the texture density gradient. Density gradients and relative densities are key features in distance perception in vertebrates. Our results suggest that they are fundamental features of vision in general, appearing also in cephalopods.